2016
DOI: 10.1055/s-0036-1580614
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Alterations in Children Infected by Human Immunodeficiency Virus Verified Through Auditory Processing Test

Abstract: Introduction The auditory system of HIV-positive children may have deficits at various levels, such as the high incidence of problems in the middle ear that can cause hearing loss. Objective The objective of this study is to characterize the development of children infected by the Human Immunodeficiency Virus (HIV) in the Simplified Auditory Processing Test (SAPT) and the Staggered Spondaic Word Test. Methods We performed behavioral tests composed of the Simplified Auditory Processing Test and the Portuguese v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Following full text review, 37 articles were excluded as they did not meet inclusion and exclusion criteria (Table 1). The remaining five articles [5,23,24,31,32] were retained for this review. Table 2 summarises key characteristics of each article.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following full text review, 37 articles were excluded as they did not meet inclusion and exclusion criteria (Table 1). The remaining five articles [5,23,24,31,32] were retained for this review. Table 2 summarises key characteristics of each article.…”
Section: Resultsmentioning
confidence: 99%
“…Although the study sample sizes ranged from 15 to 244 children, auditory processing skills were not measured in all the subjects. Three of the studies included control groups [23,24,32], while two studies reported case series [5,31]. The studies were all conducted in urban settings, in developing countries, with three of the studies based in Brazil (South America) and the other two studies based respectively in Tanzania (Africa) and Mexico (North America).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…HIV and TB infections are common in sub Saharan Africa and may increase the burden of HL. HIV is known to increase the risk of both peripheral and central hearing loss among the exposed children by causing abnormal auditory processing [7]. However, there is limited research in sub Saharan Africa where the burden of HIV infection is high.…”
Section: Introductionmentioning
confidence: 99%